Professionals calling in lifelong learning centers - Victor Seco; Miguel Pereira Lopes (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: This study aims to understand how the way people see their work and the authentizotic character of their organizational climate contribute to the building of a Great Place to Work. Design/methodology/approach: This paper presents the results of a quantitative investigation that correlate the perceptions of organizational climate and the work orientations of professionals with different occupations on Portuguese lifelong education centers. Findings: The study indicates that all the core elements of an authentizotic organization contribute to explain what people potentially expect from their companies: adequate material conditions plus a meaningful contribution. Practical implications: The study has implications in the future for National Qualification Agency directors, education politicians and human resource managers who are responsible for providing good expectations within a healthy context of talent retention. Originality/value: The novel contribution of this paper is the finding that employee's work orientations and authentizotic climate are related to each other in a Lifelong learning Center in the public education sector.
Keywords: 650; work orientation; authentizotic organizational climates; great places to work; lifelong learning